Еconomic costs on the change of organizational and legal forms of economic decrease by recording of the Сivil code of Ukraine and cancellation of the Economic code of Ukraine: to discussion - Заблодська, Iнна Володимирівна; Zablodska, Inna V.; Заблодська, І. В.; Подцерковний, Олег Петрович; Подцерковний, О. П.; Podtserkovnyi, Oleh P.; Заблодська, Дар'я Вадимівна; Заблодська, Д. В.; Zablodska, D. V.; Zablodska, Daria V.; Zablodska, I. V. (Одеса : ІПРЕЕД НАН України, 2020)
Today, the scientific environment discusses a legislative proposal to abolish the Economic Code of Ukraine and enshrined in the recodified Civil Code of Ukraine types of organizational and legal forms of management based on corporate rights.

Сьогодні у науковому середовище активно обговорюється законодавча пропозиція щодо скасування Господарського Кодексу України та закріплення у рекодифікованому Цивільному Кодексі України видів організаційно-правових форм господарювання на основі корпоративних прав.
Zablodska I. V. Еconomic costs on the change of organizational and legal forms of economic decrease by recording of the Сivil code of Ukraine and cancellation of the Economic code of Ukraine: to discussion / I. V. Zablodska, O. P. Podtserkovnyi, D. V. Zablodska // Економічні інновації : зб. наук. пр. – Одеса : ІПРЕЕД НАН України, 2020. – Т. 22, 1 (74). – С. 80-87.
Keywords: economic losses; organizational and legal form of management; legal entity; економічні втрати; організаційно-правова форма господарювання; юридична особа; Research Subject Categories::LAW/JURISPRUDENCE